(untitled) (Journal of the College of Basic Education, 2026)
The importance of studying figures who reflect the impact of historical events in a historical period is highlighted for a deeper understanding of events, drawing lessons based on the stances embodied by the event, as well as enhancing critical thinking and national identity. These figures are human models who influenced the course of events, and studying their biographies contributes to anticipating the future with insightful vision and deepening our understanding of the cultural, political, and social contexts that contributed to studying our current reality. They represent stances of great importance, and they took shrines and tombs as an eternal veil embodying their immortal heroism throughout the years.